Body image avoidance affects interpersonal distance perception: A virtual environment experiment. (16th December 2019) - Welsch, Robin; Hecht, Heiko; Kolar, David R.; Witthöft, Michael; Legenbauer, Tanja
Abstract: Objective: Eating disorders have a considerable influence on social contacts. The avoidance towards the own body may result in the avoidance of others. Previous research has found a preference for larger interaction distances in individuals with eating disorders (ED) as compared to control participants (CG). We aimed to replicate these findings and to investigate whether the body weight of the interactant moderates the effect. Method: We recruited a female sample with mixed ED subtypes ( n = 21) and a female CG ( n = 28). Participants were immersed in a virtual environment and engaged in a number of fictitious social interactions. They approached a virtual person until a comfortable distance for interaction was reached. The approached virtual persons differed with respect to body weight in five levels (underweight to obese). Results: Our results indicate that interpersonal distance varies as a U‐shaped function of the avatar's body weight, and that higher levels of body avoidance, present in ED individuals, magnify this effect. Conclusions: We discuss our results with regard to the role of perspective and disgust to provide a useful framework and to motivate future studies in the domain of body avoidance in social interactions.